2003
DOI: 10.1007/s00268-002-6816-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human Pancreatic Cancer in Mice with Angiogenic Inhibitors

Abstract: Tumor growth is dependent on the balance of positive and negative regulators of angiogenesis. Antiangiogenic compounds inhibit endothelial cell biology in vitro and angiogenesis in vivo. Therefore antiangiogenic therapy presumes to be an effective treatment for pancreatic cancer. We wanted to determine the effect of antiangiogenic therapy on the growth of human pancreatic cancer in a mouse model. The angiogenesis inhibitors TNP-470 and antiangiogenic antithrombin III (aaATIII) were tested in vitro for their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
3
35
0
1
Order By: Relevance
“…Nevertheless, the greater antiangiogenic potency of prelatent antithrombin over latent and cleaved forms and the conditions we have established for producing this species suggest potential clinical applications for antitumor therapy. This is underscored by the fact that the antiangiogenic activity of cleaved and latent forms of antithrombin is already comparable with that of other well established angiogenesis inhibitors, such as endostatin and TNP-470 (16,20).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the greater antiangiogenic potency of prelatent antithrombin over latent and cleaved forms and the conditions we have established for producing this species suggest potential clinical applications for antitumor therapy. This is underscored by the fact that the antiangiogenic activity of cleaved and latent forms of antithrombin is already comparable with that of other well established angiogenesis inhibitors, such as endostatin and TNP-470 (16,20).…”
Section: Discussionmentioning
confidence: 93%
“…Such conformational alterations transform the native metastable protein to a much more stable but inactive form in which the reactive loop has inserted into the major ␤-sheet, the A-sheet, of the serpin (17,18). These conformationally altered forms of antithrombin are produced under physiologic conditions (19) and have antiangiogenic activity comparable with that of other naturally produced angiogenesis inhibitors (20). The requirement for conformational change to generate antiangiogenic activity sets antithrombin apart from other serpins, such as pigment epithelium-derived factor, maspin, and kallistatin, which have been shown to also possess antiangiogenic activity but without the need for conformational change (21)(22)(23).…”
mentioning
confidence: 96%
“…Actually, a synergy between thrombospondin-1 and anti-VEGF small interfering RNA had been reported using a mouse fibrosarcoma model (44). Endostatin is another endogenous angiogenesis inhibitor, which showed therapeutic effects in s.c. pancreatic cancer models (45,46). Because endostatin and thrombospondin-1 exert antiangiogenic activity via different pathways (19), therapeutic contributions of these agents may be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 2 and VEGF (5,9,14). Previous results including those from our group have demonstrated that cleaved and latent forms of antithrombin exert their antiangiogenic effects by inducing cell apoptosis (9,15,16), inhibiting endothelial cell cycle progression (17), and suppressing the expression of the proangiogenic heparan sulfate proteoglycan (HSPG) perlecan, as well as other proangiogenic genes in cultured HUVECs (16,17). However, the molecular mechanisms of antithrombin antiangiogenic action still remain to be defined.…”
Section: Cleaved and Latent But Not Native Forms Of Antithrombin Blocmentioning
confidence: 99%